The COMET toolkit for composing customizable genetic programs in mammalian cells - Patrick S. Donahue (Nature Portfolio, 2020)
Engineering mammalian cellular functions requires a toolkit of orthogonal and well-characterized genetic components. Here the authors develop COMET: an ensemble of transcription factors, promoters, and accompanying models for the design and construction of genetic programs.